Gram-Negative Bacteria from Organic and Conventional Agriculture in the Hydrographic Basin of Loja: Quality or Pathogen Reservoir? - Darío Cruz; Rodrigo Cisneros; Ángel Benítez; Wilson Zúñiga-Sarango; Jhoan Peña; Heriberto Fernández; Andrea Jaramillo (Agronomy, 2021)
Organic and conventional agriculture are vital for the development of human society; however, the use of contaminated water and the inappropriate use of organic chemical fertilizers can lead to an increase in the microbial load (potentially pathogenic) of the normal microbiota of the agricultural soil. In this context, the aim of our study was to isolate Gram-negative bacteria from the superficial soil layer and irrigation water of agricultural areas (11 organic farms and nine conventional farms) and consider their potential ecological and health risk importance. Through culture isolation using three bacterial media (TSA) trypticase soy agar (general nutritive media); MacConkey Gram-negative bacteria and (EMB) eosin methylene blue agar (selective for Enterobacteriaceae) and classical biochemical tests, we recorded a total of 12 bacterial species, most belonging to the Enterobacteriaceae family, such as Enterobacter, Escherichia, Klebsiella, Salmonella and Shigella, which can be pathogenic for humans and animals. In contrast, bacteria such as Pantoea agglomerans, Pseudomonas aeruginosa, P. fluorescens and Burkholderia mallei could facultatively work as diazotrophic or plant growth-promoting rhizobacteria. Soil bacteria richness detected with the media applied was significantly higher than water bacteria, but we found no significant differences between organic and conventional agriculture. We conclude that the isolated bacteria in water and soil mostly belongs to enteropathogenic bacteria which could be pathogenic to animals and humans. While other bacteria like Pseudomonas aeruginosa could be viewed as useful by improving nutrient availability in agricultural soil.